Climate in Surkhandarya Region and Some Issues of Climate Impact on Human Health - Mamatkulova Mayaguzal Yalkopberdiyevna (Indonesian Journal of Public Policy Review, 2022)
This article examines climate in Surkhandarya region and some issues of climate impact on human health, in which Termez and Denot districts are considered separately, as well as a table related to disease outbreaks.